On the Road to Individualization of Vaccination: the Significance of Age and Sex - B. V. Karalnik (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. The high variability of protection against vaccine-controlled infections, including COVID-19, is one of the actual problem of infectology. Aim. Based on the results of scientific publications and reports, the role of age and sex factors, their interactions and the main mechanisms in the immune response to vaccines, in the improvement of vaccines and vaccination regimens, has been analyzed. Conclusion. It has been shown that vaccine prophylaxis has always developed in the direction of individualization, going through the stages of defining target groups and developing immunization schemes for various groups. The important data obtained in recent decades on the importance of genetic and external factors, in particular, age and sex, in the variability of response to vaccines are analyzed. Analysis of the role of such factors has also been performed for coronavirus vaccines. The necessity and possibilities of next steps that can provide optimal responses of different people to vaccination were discussed.